OPTIMALISASI KEBERLANJUTANPENGEMBANGAN USAHA PADI ORGANIK DI KABUPATEN CIANJUR, JAWA BARAT - Anita Ristianingrum; M. A. Chozin; Machfud Machfud; Sugiyanta Sugiyanta; Sri Mulatsih (Jurnal Manajemen & Agribisnis, 2016)
The purpose of this study were to assess the sustainability status of organic rice businesses and their attributes that affect the sustainability of the businesses in Cianjur. The methods used in this study were surveys and in-depth interviews. Moreover, Rap-Organic/multi-dimensional scaling as the analysis tools were also utilized to assess the sustainability of the organic rice businesses. The analysis conducted indicates that sustainability status of organic rice businesses in Cianjur is less sustainable reflected in all dimensions i.e. the dimensions of ecology, economy, social, infrastructure and technology, as well as institutions. Aggregately, the sensitive attributes influencing the sustainability of organic rice business bussinesses can be classified into three factors: 1) human resources of farmers, 2) institutions (the government policies related to the organic rice businesses and infrastructure support), and 3) organic rice market.Keywords: organic rice businesses, sustainability, sensitive attributes, Rap-Organic